SIFAT ARANG EMPAT JENIS BAMBU - Tjutju Nurhayati Syahri (Jurnal Penelitian Hasil Hutan, 1986)
Studies on the properties  of bamboo  charcoal processed  by destructive  distillation  has been conducted.  Four different  species of bamboo have been selected,  i.e. andong  (Gigantochloa vertivillata  Munro),  ater (G. ater Kurz),  tali  (G. apus Kusz),  and  bitung  (Dendrocalamus asper  Back), were obtained from  Kabupaten  Bogor.  The properties  of interest  are: the specific gravity, calorific value, ash content,  volatile  matter,  and  the  fixed  carbon content  on three different  parts  of bamboo  trunk  (bottom,  middle,  and top).The specific gravity and the properties  of the destructive  distillation products from  each part of bamboo  trunk  were significantly  different. The lowest part of bamboo  trunk revealed the highest yield and the highest density of charcoal. In contrast,  the yield of piroligneous ligour  gave a tendency of decreasing toward  the lowest part of bamboo  trunk; exception was found  in bamboo ater and tali, which indicated the highest content  in  the middle part  of  the trunk.All four  different  species of bamboo gave fairly  the same yield of destructive distillation products.  The average yield of charcoal, the content of piroligneous ligour , and the tar content  were 36.05,  40.58, and 6,550'/o,   respectively.The specific gravity of all four  different  charcoal were significantly  different,  the highest  was found   in ater charcoal (0. 6), and the lowest was in bitung  (0.3).  The highest ash content  was found   in bitung charcoal (7.50'/o), and  the lowest  was indicated  by tali charcoal (5. 70'/o).  The highest  volatile matter  was in tali charcoal (24.40'/o), and the lowest content  was in bitung  (/7.800'/o). The highest and the lowest fixed  carbon content  were found   in bitung (75. 50'/o) and tali charcoal (69. 80'/o ), respectively.There were no great differences  in calorific  value for  all different  species of bamboo,  with the average of 6602 ca/lg  charcoal. However, different part of bamboo  trunk indicated significantly  different  calorific  value, that is, the higher the position  in the trunk,  the lower the calorific value.